Aortic valve replacement after iatrogenic injury related to an Impella device. (June 2021) - Saitoh, Daiki; Kin, Hajime
The Impella device is used routinely during coronary interventions, and device-related iatrogenic injury requiring surgical repair is rarely reported. We report a case of iatrogenic aortic valve injury due to Impella device insertion, necessitating aortic valve replacement surgery. A 55-year-old woman with acute anteroseptal myocardial infarction underwent a successful percutaneous coronary intervention and Impella insertion for hemodynamic support. Four months later, she experienced congestive heart failure; transthoracic echocardiography revealed new-onset severe aortic insufficiency. Aortic valve replacement was performed without complications. Follow-up transthoracic echocardiography should be performed after Impella removal to avoid delay in treating residual aortic insufficiency.